The influence of digestate concentration during cultivation on the quality of biogas obtained from the anaerobic digestion of duckweed (Spirodela polyrhiza) - Matošević, Damir, inženjer agronomije (Array, 2019)
Duckweed is a widespread type of tiny free-floating plants of the flowering class. A typical representative of the family of the cowhide (Lemnaceae) is a large duckweed (Spirodela polyrhiza) and it is very common on Croatian inland waters. Like all other species of duckweeds, it is characterized by the possibility of vegetative and sexual reproduction and very rapid growth. It has the ability to remove nitrogen, phosphorus and some heavy metals from the substrate and is considered a very desirable raw material for biogas production for several reasons. The necessity of reducing environmental pollution of nitrates from agricultural production and the ability to grow water lenses under eutrophic conditions have sparked this research. The primary objective of the study is to determine the possibilities of continuously growing large duckweed at different concentrations of digestates for the purpose of biogas production. The secondary goal is to determine the dependence between the different digestate concentrations used for the duckweed green mass production and the quantity and quality of the biogas obtained through the anaerobic digestion process at thermophilic conditions.